New species of toad, genus Frostius Cannatella, 1986, from the Atlantic Rain Forest of Bahia, Brazil (Amphibia, Anura, Bufonidae) - Pimenta, Bruno V.s.; Caramaschi, Ulisses (Zootaxa, 2007)
A new species of the previously monotypic bufonid genus Frostius is described from Atlantic Rain Forest fragments in the southern region of the State of Bahia, Brazil. The new species is distinguished from F. pernambucensis by life colors of body and iris, length and width of digits, development of apical discs, and size and shape of tympanum. New locality records extend the distribution of the genus 105 km to the north (to the State of Paraíba), and 190 km to the south (southern region of the State of Bahia).